Path Diagram of the Reputation of Faculties of Social Work in Central Mexico - GarcÃa Lirios, Cruz (Journal of Techno-Social, 2022)
Corporate governance as a knowledge management system has been approached from the organizational reputation as a result of alliances with institutions. In the health sector, the demand for a quality service has led to a system of professional practices and deregulated social service in which the image of the universities and health centers involved is questioned. The objective of the present work was to contrast a model for the study of the phenomenon with the intention of specifying the relationships between variables. A non-experimental exploratory and cross-sectional study was conducted with a non-probabilistic and intentional sample of 1018 administrative, professional and students of the health sector. It was found that the follow-up factor of cases reflected the image of the universities as trainers of intellectual capital by competences. In relation to the literature consulted, research lines are proposed to specify the model.